Analisis Depresiasi Aktiva Tetap Metode Garis Lurus dan Jumlah Angka Tahun PT Adira Dinamika - Dian Indah Sari (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2018)
Abstract - This study aim to analiyze the calculation of depreciation expenses using the straight line method and year number method at PT Adira Dinamika Multi Finance Tbk. This study uses three types ot data collection namely the study of literature namely obtaining data though literature sources, like a book which support the theoretical foundation of fixed asset and writing content. Non behavior observation namely obtaining data through observation of financial statements, published by Ardhi Karya (Persero) tbk during 2015. The conclution is that the  d expenses of fixed asset using the straight line method will give the same depreciation burden every year. 2) the calculation of depreciation expenses of fixed asset using year numbermethod will give depreciation burden decreased annualy.Keywords : Depreciation, Fixed Asset, Straight Line, Number of Years.